Contemporary conflict resolution : the prevention, management and transformation of deadly conflicts - Miall, Hugh. (Polity Press, 1999)
Introduction. Conflict resolution: foundations, constructions and reconstructions. Understanding contemporary conflict. Preventing violent conflict. Working in war zones. Ending violent conflict...